The impact of electronic stores’ use of information technology on customer satisfaction: The case of Amazon company E-marketing - Abu Al-Rub, Abdelmo’ti Suleiman Abdelmo’ti (Journal of Economic, Administrative and Legal Sciences, 2019)
Information and technology (IT) is considered as an important component of business activity because it provides accurate information that helps senior management accelerate their decision-making. It is worth noting that information technology and its uses are constantly changing, making it important to accommodate to all these changes. Therefore, it is imperative for business organizations, including electronic stores, to exploit them to achieve the maximum benefit so that it can achieve its goals and satisfy its customers. Hence, the problem of this study is to investigate the impact of the use of electronic stores of information technology on customer satisfaction? The importance of the study stems from the fact that it addresses an important element worthy of study, knowing the impact of electronic stores’ use of information technology on customer satisfaction. The study was based on the following main hypothesis: There is no statistically significant effect at (α = 0.05) level between IT and customer satisfaction. According to the study’s objectives and hypotheses, a questionnaire was designed and distributed to a random sample including 250 customers of Amazon Electronic Marketing Company in Riyadh. A descriptive analytical method was used in data analysis according to the literature review dealing with the topic of the study. Therefore, the study recommended the concerned parties to use information technology in their management strategies and activities because of the benefits provided by information technology in improving the quality of services provided to customers, which, in return, impacts positively on their satisfaction.